Improved performance of phosphonated carbon nanotube-polybenzimidazole composite membranes in proton exchange membrane fuel cells - Kannan, Ramaiyan; Kagalwala, Husain N.; Chaudhari, Harshal D.; Kharul, Ulhas K.; Kurungot, Sreekumar; Pillai, Vijayamohanan K. (Journal of Materials Chemistry, 2011)
Development of thermally stable polymer electrolyte membranes with higher proton conductivity as well as mechanical stability is a key challenge in commercializing PEM fuel cells operating above 100 degrees C. Polybenzimidazole membranes are one of the promising candidates in this category although with limited mechanical stability and moderate proton conductivity. Here the incorporation of functionalized MWCNT is shown to increase both these key parameters of the polybenzimidazole membranes. Further, formation of a domain like structure after the incorporation of phosphonated MWCNTs (P-MWCNTs) in phosphoric acid doped polybenzimidazole membranes is demonstrated. The enhanced performance has been attributed to the formation of proton conducting networks that formed along the sidewalls of P-MWCNTs with a domain size of 17 nm as estimated from the small angle X-ray scattering measurements. Membrane electrode assembly (MEA) impedance measurements further reveal that the activation energy of oxygen reduction reaction (ORR) reduced for the composite membranes with enhanced proton conductivity. In addition, the mechanical strength measurements reveal a significant improvement in the yield strength and ultimate strength. Also, the mechanical strength of the composite membrane has been increased significantly as indicated by the improvement in the ultimate strength from 65 MPa to 100 MPa for the pristine and composite membranes, respectively. The optimum loading of P-MWCNTs is found to be 1% as inferred from the polarization measurements carried out using pure hydrogen and oxygen. Thus, this study provides a unique opportunity to tune the properties of polymer electrolytes to prepare application oriented hybrid membranes using CNTs with tailor-made functional groups.

Interlayer hydrogen-bonded covalent organic frameworks as high-performance supercapacitors - Halder, Arjun; Ghosh, Meena; Khayum, Abdul M.; Bera, Saibal; Addicoat, Matthew; Sasmal, Himadri Sekhar; Karak, Suvendu; Kurungot, Sreekumar; Banerjee, Rahul (Journal of the American Chemical Society, 2018)
Covalent organic frameworks (COFs) have emerged as promising electrode materials in supercapacitors (SCs). However, their insoluble powder-like nature, poor capacitive performance in pristine form, integrated with inferior electrochemical stability is a primary concern for their long-term use in electrochemical devices. Keeping this in perspective, herein we report a redox active and hydrogen bonded COF with ultrahigh stability in conc. H2SO4 (18 M), conc. HCl (12 M) and NaOH (9 M). The as-synthesized COF fabricated as thin sheets were efficiently employed as a free-standing supercapacitor electrode material using 3 M aq. H2SO4 as an electrolyte. Moreover, the pristine COF sheet showcased outstanding areal capacitance 1600 mF cm(-2) (gravimetric 169 F g(-1)) and excellent cyclic stability (>100 000) without compromising its capacitive performance or Coulombic efficiency. Moreover, as a proof-of-concept, a solid-state supercapacitor device was also assembled and subsequently tested.

Iron Catalyzed Hydroformylation of Alkenes under Mild Conditions: Evidence of an Fe(II) Catalyzed Process - Pandey, Swechchha; Raj, K. Vipin; Shinde, Dinesh R.; Vanka, Kumar; Kashyap, Varchaswal; Kurungot, Sreekumar; Vinod, C. P.; Chikkali, Samir H. (Journal of the American Chemical Society, 2018)
Earth abundant, first row transition metals offer a cheap and sustainable alternative to the rare and precious metals. However, utilization of first row metals in catalysis requires harsh reaction conditions, suffers from limited activity, and fails to tolerate functional groups. Reported here is a highly efficient iron catalyzed hydroformylation of alkenes under mild conditions. This protocol operates at 10-30 bar syngas pressure below 100 degrees C, utilizes readily available ligands, and applies to an array of olefins. Thus, the iron precursor [HFe(CO)(4)](-)[Ph3PNPPh3](+) (1) in the presence of triphenyl phosphine catalyzes the hydroformylation of 1-hexene (S2), 1-octene (S1), 1-decene (S3), 1-dodecene (S4), 1-octadecene (S5), trimethoxy(vinyl)silane (S6), trimethyl(vinyl)silane (S7), cardanol (S8), 2,3-dihydrofuran (S9), allyl malonic acid (S10), styrene (S11), 4-methylstyrene (S12), 4-iBu-styrene (S13), 4-tBu-styrene (S14), 4-methoxy styrene (S15), 4-acetoxy styrene (S16), 4-bromo styrene (S17), 4-chloro styrene (S18), 4-vinylbenzonitrile (S19), 4-vinylbenzoic acid (S20), and allyl benzene (S21) to corresponding aldehydes in good to excellent yields. Both electron donating and electron withdrawing substituents could be tolerated and excellent conversions were obtained for S11-S20. Remarkably, the addition of 1 mol % acetic acid promotes the reaction to completion within 16-24 h. Detailed mechanistic investigations revealed in situ formation of an iron-dihydride complex [H2Fe(CO)(2)(PPh3)(2)] (A) as an active catalytic species. This finding was further supported by cyclic voltammetry investigations and intermediacy of an Fe(0)-Fe(II) species was established. Combined experimental and computational investigations support the existence of an iron-dihydride as the catalyst resting state, which then follows a Fe(II) based catalytic cycle to produce aldehyde.

Imidazole-linked crystalline two-dimensional polymer with ultrahigh proton-conductivity - Ranjeesh, Kayaramkodath Chandran; Ilathvalappil, Rajith; Veer, Sairam Dnyaneshwar; Peter, Joseph; Wakchaure, Vivek Chandrakant; Goudappagouda; Raj, K. Vipin; Kurungot, Sreekumar; Babu, Sukumaran Santhosh (Journal of the American Chemical Society, 2019)
Proton-exchange membrane fuel cells are promising energy devices for a sustainable future due to green features, high power density, and mild operating conditions. A facile proton-conducting membrane plays a pivotal role to boost the efficiency of fuel cells, and hence focused research in this area is highly desirable. Major issues associated with the successful example of Nafion resulted in the search for alternate proton conducting materials. Even though proton carrier loaded crystalline porous organic frameworks have been used for protonconduction, the weak host-guest interactions limited their practical use. Herein, we developed a crystalline 2D-polymer composed of benzimidazole units as the integral part, prepared by the condensation of aryl acid and diamine in polyphosphoric acid medium. The imidazole linked-2D-polymer exhibits ultrahigh proton conductivity (3.2 X 10(-2) S cm(-1)) (at 95% relative humidity and 95 degrees C) in the pristine state, which is highest among the undoped porous organic frameworks so far reported. The present strategy of a crystalline proton-conducting 2D-polymer will lead to the development of new high performing crystalline solid proton conductor.

In-situ generated Mn3O4-reduced graphene oxide nanocomposite for oxygen reduction reaction and isolated reduced graphene oxide for supercapacitor applications - Jha, Plawan Kumar; Kashyap, Varchaswal; Gupta, Kriti; Kumar, Vikash; Debnath, Anil Krishna; Roy, Debashree; Rana, Shammi; Kurungot, Sreekumar; Ballav, Nirmalya (Carbon, 2019)
We have generated in situ nanocomposite of Mn3O4 and reduced graphene oxide (rGO) upon employing wet-chemical reduction of graphene oxide (GO) by Mn(II) salt as mild-reducing agent for the first time and examined the oxygen reduction reaction (ORR) activity in 0.1 M KOH electrolyte. The half-wave potential (E-1/2) of the nanocomposite catalyst (20% Mn3O4-rGO/C) was found to be around -0.153 V which is only similar to 87 mV negative from the commercially available catalyst (20% Pt/C). Remarkably, after 5000 linear sweep voltammetry cycles the E-1/2 shifted marginally by 20 mV; and the number of electrons transferred during ORR was estimated to be close to 4. Such an efficient electrocatalytic performance of the nanocomposite was primarily attributed to the synergistic interaction between Mn3O4 and rGO. The fabricated all-solid-state supercapacitor of rGO (extracted from the nanocomposite) in aqueous polyvinyl alcohol-sulfuric acid (PVA-H2SO4) gel polymer electrolyte (GPE) showed C-s value of similar to 310 F/g at a current density of 1 A/g along with long durability (10,000 charge-discharge cycles). All-solid-state flexible rGO supercapacitor exhibited high-flexibility and excellent durability (30,000 cycles with 100% retention of C-s). Our results provide an enormous opportunity in designing transition metal oxides decorated semiconducting reduced graphene oxide nanocomposite platforms for various electrochemical applications. (C) 2019 Elsevier Ltd. All rights reserved.

In situ cross-linked nonaqueous polymer electrolyte for zinc-metal polymer batteries and hybrid supercapacitors - Vijayakumar, Vidyanand; Ghosh, Meena; Kurian, Maria; Torris, Arun; Dilwale, Swati; Badiger, V. Manohar; Winter, Martin; Nair, Jijeesh Ravi; Kurungot, Sreekumar (Small, 2020)
This work reports the facile synthesis of nonaqueous zinc-ion conducting polymer electrolyte (ZIP) membranes using an ultraviolet (UV)-light-induced photopolymerization technique, with room temperature (RT) ionic conductivity values in the order of 10(-3)S cm(-1). The ZIP membranes demonstrate excellent physicochemical and electrochemical properties, including an electrochemical stability window of >2.4 V versus Zn|Zn(2+)and dendrite-free plating/stripping processes in symmetric Zn||Zn cells. Besides, a UV-polymerization-assisted in situ process is developed to produce ZIP (abbreviated i-ZIP), which is adopted for the first time to fabricate a nonaqueous zinc-metal polymer battery (ZMPB; VOPO4|i-ZIP|Zn) and zinc-metal hybrid polymer supercapacitor (ZMPS; activated carbon|i-ZIP|Zn) cells. The VOPO(4)cathode employed in ZMPB possesses a layered morphology, exhibiting a high average operating voltage of approximate to 1.2 V. As compared to the conventional polymer cell assembling approach using the ex situ process, the in situ process is simple and it enhances the overall electrochemical performance, which enables the widespread intrusion of ZMPBs and ZMPSs into the application domain. Indeed, considering the promising aspects of the proposed ZIP and its easy processability, this work opens up a new direction for the emergence of the zinc-based energy storage technologies.
Keywords: nonaqueous electrolytes; polymer electrolytes; postlithium batteries; Supercapacitors; zinc-metal batteries

In situ polymerization process: an essential design tool for lithium polymer batteries dagger - Vijayakumar, Vidyanand; Anothumakkool, Bihag; Kurungot, Sreekumar; Winter, Martin; Nair, Jijeesh Ravi (Energy & Environmental Science, 2021)
Polymer electrolytes (PEs), a type of solid-state electrolytes (SSEs), have been in contention for nearly half a century to replace organic liquid electrolytes (LEs) that are used in state-of-the-art lithium-ion batteries (LIBs). They are envisaged to accelerate the industrial-scale production of safe, energy-dense, flexible, and thin lithium polymer batteries (LPBs). LPBs are expected to be widely employed for electric propulsion and other futuristic applications, such as flexible electronics and the Internet of Things (IoT). Even though several polymer architectures and chemistries have been attempted so far, PEs that can outperform LEs remain a real challenge. Apart from inadequate Li+-ion transport properties, challenges concerning the integration of PEs and the engineering of compatible, robust, and durable interfaces and interphases at both the electrodes of LPBs must be appropriately addressed. Recently, the in situ polymerization process has been widely employed as a robust fabrication tool for surpassing the intricacies related to the integration of PEs in LPBs. Hence, in this review, we focus on the in situ polymerization processes that employ various polymerization methods (e.g., free-radical polymerization, ionic polymerization, electropolymerization, condensation polymerization, etc.), functional monomers and oligomers (e.g., acrylate, methacrylate, allyl and vinyl ethers, epoxides, etc.), and PE integration strategies for the fabrication of lithium (ion and metal) polymer batteries (LIPBs and LMPBs). Additionally, this review also evaluates the approaches that have been developed until now to implement the in situ processing of LPBs from large-sized pouch cells to flexible-/printable-batteries and even microbatteries.

In situ preparation of ionomer as a tool for triple-phase boundary enhancement in 3D graphene supported Pt catalyst - Gangadharan, Pranav K.; Vijayakumar, Vidyanand; Nediyirakkal, Shijil A.; Fernandez, Roshni Tresa; Siddharthan, V. Adhrika; Kurungot, Sreekumar (Advanced Sustainable Systems, 2021)
For improving the performance of platinum electrocatalysts in polymer electrolyte membrane fuel cells (PEMFCs), it is important to enhance the Pt utilization level in the catalyst systems. A high performing electrocatalyst (Pt/3DNG) is developed for PEMFC applications by using nitrogen-doped 3D graphene (3DNG) as the support material and an in situ grafted active ``triple-phase boundary'' to more precisely control the formation of the proton conducting ionomer interface at the active sites. Considering the 3D morphology of the system, during the electrode fabrication for realistic single-cell evaluation, the concept of in situ generation of the proton conducting-ionomer based ``active triple-phase boundary'' is introduced, which could potentially replace the conventional method of using Nafion ionomer for the electrode preparation. The monomers owing to their small-size can access the pores and inner regions of the 3DNG support, which on UV-curing, undergo polymerization and transform into an ionomer with an extended interfacial network into the nanoregimes of 3DNG. Single cell evaluation of the membrane electrode assembly in a high-temperature PEMFC by using phosphoric acid doped polybenzimidazole membrane demonstrates the utility of the present strategy.
Keywords: electrocatalysts; fuel cells; graphene; oxygen reduction reaction

Interconnected polyaniline nanostructures: enhanced interface for better supercapacitance retention - Mooss, Vandana A.; Vijayakumar, Vidyanand; Kurungot, Sreekumar; Athawale, Anjali A. (Polymer, 2021)
Polyaniline and its nanocomposites have emerged as desirable electrode materials for supercapacitors. However, achieving specific capacitance with long-term cyclic stability is still a challenge. The present study reports on novel hierarchically porous and cross-linked polyaniline synthesized by a method employing aniline (monomer) and phytic acid (dopant acid) in the presence of octyltrimethyl ammonium bromide (OTAB) surfactant. The electrochemical performance of the phytic acid doped sample has been compared with HCl doped samples, the former being superior, i.e., a specific capacitance of 523 and 325 F g(-1) at current densities of 0.25 and 10 A g(-1), respectively. Additionally, the same possess excellent cycling stability with retention of similar to 88% of its initial capacitance over 10,000 charge-discharge cycles. Further, the phytic acid doped sample exhibited a lower equivalent series resistance (0.98 Omega cm(2)) than the HCl doped sample (1.26 Omega cm(2)). These results reveal the capability of the phytic acid doped hierarchical polyaniline sample as a promising active material for electrochemical applications.
Keywords: Cyclic stability; Hierarchical polyaniline; Supercapacitance retention

Influence of ice templating on oxygen reduction catalytic activity of metal-free heteroatom-doped mesoporous carbon derived from polypyrrole for zinc-air batteries - Kurian, Maria; Ghosh, Meena; Vijayakumar, Vidyanand; Puthiyaveetil, Priyanka Pandinhare; Torris, Arun; Kurungot, Sreekumar (Energy Technology, 2022)
The development of highly active, cost-effective, and durable, noble metal-free oxygen reduction electrocatalysts is inevitable for the full-fledged implementation of fuel cells and zinc-air batteries. This work reports the synthesis of heteroatom (N, P, S)-doped metal-free mesoporous carbon-based electrocatalyst derived from polypyrrole by combining the ice templating, freeze-drying, and carbonization processes. The correlation between the structure and electrochemical activity of the polypyrrole-derived carbon-based electrocatalyst in the presence and absence of ice templating is investigated. The optimized electrocatalyst, aided by the ice-templating and freeze-drying step, shows an onset and half-wave potential (E-1/2) of 0.94 and 0.78 V vs reversible hydrogen electrode, respectively, in an alkaline electrolyte (0.1 m KOH). Later, the application of the optimized electrocatalyst is demonstrated in a primary zinc-air battery (ZAB) cell. The results prove that the ZAB device performance based on the homemade catalyst is on par with that of the state-of-the-art Pt/C cathode. The catalyst performance is correlated with the heteroatom doping and the enhanced porosity of the sample benefitted from ice templating. Ultimately, this work depicts a facile and rational synthesis of a truly metal-free electrocatalyst for the primary ZABs that can be a potential replacement for state-of-the-art systems.
Keywords: metal-free electrocatalysts; oxygen reduction reaction; zinc-air batteries

Insights on prussian blue analogue cathode material engineered with polypyrrole surface protection layer for aqueous rechargeable zinc metal battery - Puthiyaveetil, Priyanka Pandinhare; Nair, Aathira; Dilwale, Swati; Kurian, Maria; Joshi, Kavita; Kurungot, Sreekumar (Small, 2024)
One of the key intricacies against using Prussian blue analogues (PBAs) in aqueous batteries is their gradual dissolution in aqueous electrolytes, resulting in inadequate cycling stability. Besides, the rate capability of PBAs is limited due to their poor electrical conductivity. To overcome these challenges, it is essential to tune the physical and chemical properties of PBAs at the nano regime without affecting the inherent charge storage properties, especially at high-voltage operating conditions. Through this work, a strategy is demonstrated to enhance the electrochemical performance of vanadium-based PBA (V-PBA) by surface engineering using a conducting polymer nano-skin (V-PBA/PPy) for aqueous zinc metal batteries. The polypyrrole (PPy) nano-skin over the V-PBA nanoparticles acts as an electron percolation path to ameliorate the poor electronic conductivity of the otherwise pristine V-PBA. Interestingly, the V-PBA with an optimized polypyrrole coating (V-PBA/PPy-2) exhibits an enhanced specific capacity (173 mAh g-1 at 0.10 A g-1) than the pristine V-PBA counterpart (80 mAh g-1) and 85% capacity retention up to 500 cycles. The DFT calculation confirms the synergistic interaction between PPy and V-PBA and the presence of PPy favors the adsorption of Zn.
Keywords: aqueous rechargeable zinc metal battery; DFT; polypyrrole coating; Prussian blue analogue; surface protection layer

Interlayer space engineering-induced pseudocapacitive zinc-ion storage in holey graphene oxide-bearing vertically oriented MoS2 nano-wall array cathode for aqueous rechargeable Zn metal batteries - Babu, Athira; Dilwale, Swati; Kurungot, Sreekumar (Small, 2024)
Transition metal dichalcogenides, particularly MoS2, are acknowledged as a promising cathode material for aqueous rechargeable zinc metal batteries (ARZMBs). Nevertheless, its lack of hydrophilicity, poor electrical conductivity, significant restacking, and restricted interlayer spacing translate into inadequate capacity and rate performance. Herein, the unique porous structure and additional functional groups present in holey graphene oxide (hGO) are taken advantage of to dictate the vertical growth pattern of oxygen-doped MoS2 nanowalls (O-MoS2/NW) over the hGO surface. Compared to conventional graphene oxide (GO), the presence of nano-pores in hGO facilitates the homogeneous dispersion of Mo precursors and provides stronger interaction sites, promoting the uniform vertical alignment of O-MoS2/NW. The synergistic interaction between O-MoS2-NW and hGO translates to enhanced electron conductivity, efficient electrolyte penetration, enhanced interlayer spacing, reduced restacking, and enhanced surface area. As a consequence of precise control of various factors that decide the overall battery performance, a high discharge capacity (227 mAh g(-1) at 100 mA g(-1)) cathode material with significantly lower charge transfer resistance (66 Omega) compared to pristine O-MoS2 (153 Omega) is developed. These findings underscore the potential of hGO as a multifunctional platform for nanoengineering high-performance cathode materials for the next generation of efficient and durable ARZMBs.
Keywords: aqueous rechargeable zinc metal battery; holey graphene oxide; hydrophilicity tuning; interlayer space engineering; oxygen-doped MoS2; transition metal dichalcogenide; vertical nanowall

Iron salicylaldehydate conjugated metal-organic framework for quasi solid-state supercapacitor - Mohammed, Abdul Khayum; Pandikassala, Ajmal; Sanchez, Pilar Pena; Gaber, Safa Abdullah; Canossa, Stefano; Kurian, Maria; Xavier, Gigi; He, Yao; Gandara, Felipe; Kurungot, Sreekumar; Shetty, Dinesh (CHEMICAL ENGINEERING JOURNAL, 2024)
Keywords: Carbon; conductivity; ELECTROLYTE CONCENTRATION; performance; ROBUST

In situ engineered triple phase boundary enhancement in 3D structured carbon supported catalyst for high-temperature PEMFC - Pandikassala, Ajmal; Jadhav, Swapnil D.; Kurian, Maria; Kurungot, Sreekumar (Journal of Materials Chemistry A, 2025)
Enhancing platinum (Pt) utilization in polymer electrolyte membrane fuel cells (PEMFCs) requires optimizing the catalyst support microstructures to expand the triple-phase boundary (TPB). A promising method has been reported here which employs a three-dimensional (3D) catalyst support with an in situ-generated ionomer interface from preadmitted monomer molecules, potentially replacing the traditional Nafion ionomers. The small-sized monomers infiltrate the catalyst's pores, and UV curing polymerizes them into an extended interfacial network within the 3D carbon support. The single-cell analysis of the membrane electrode assemblies (MEAs) in high-temperature PEMFCs (HT-PEMFCs) using phosphoric acid-doped polybenzimidazole (PBI) membranes highlights the effectiveness of this approach. The strategy helps to achieve a current density of 1.06 A cm-2 and 0.49 A cm-2 at 0.60 V in H2-O2 and H2-air feed conditions, respectively. These values represent a significant improvement over the conventional Nafion ionomer-based MEAs, which exhibit current densities of 0.87 A cm-2 and 0.40 A cm-2 under H2-O2 and H2-air feeds, respectively, when utilizing a platinum-supported carbon (Pt/C) catalyst. When Pt nanoparticles are decorated on a high-surface-area, porous 3D interconnected carbon support synthesized via the carbonization of the polydopamine-coated melamine foam (Pt/3DPDC), the conventional Nafion ionomers tend to block the nanopores in the 3D carbon supports, leading to the underutilization of the Pt active sites. In contrast, the in situ ionomer approach enabled the system to deliver 0.93 A cm-2 at 0.60 V H2-O2 feed conditions, which is significantly higher than 0.38 A cm-2 obtained with the Nafion-based ionomers under similar conditions. This approach successfully makes use of the Pt active sites present in the nanopores and tackles the issues of mass transfer and reactant distribution, both of which are essential for expanding fuel cells from single cells to stacks. The exhibited method emphasizes how crucial it is to develop process-friendly electrocatalysts and complementary electrode manufacturing techniques in order to advance the PEMFC performance through a novel scientific path.